Neural Correlates of Workload Transition in Multitasking: An ACT-R Model of Hysteresis Effect - Kim, Na Young; House, Russell; Yun, Myung H.; Nam, Chang S. (Frontiers in Human Neuroscience, 2019)
This study investigated the effect of task demand transitions at multiple levels of analysis including behavioral performance, subjective rating, and brain effective connectivity, and compared human data to Adaptive Control of Thought-Rational (ACT-R) simulated data. We created three stages of task demand that were performed sequentially (Low-High-Low) during AF-MATB tasks and identified differences in neural connectivity during workload transition. We used NASA-TLX, and ISA to measure the subjective mental workload that accompanies the hysteresis effect in the task demand transitions. We found significant hysteresis effects on performance and various brain network measures such as outflow of prefrontal cortex and connectivity magnitude. These findings would allow us to clarify the direction and strength of the Granger Causality under demand transitions. Therefore, these results involving the neural mechanisms of hysteresis effects in multitasking environments may be utilized in applications of neuroergonomics research. Furthermore the ability to compare data derived from human participants to data gathered by the ACT-R model allows researchers to better account for hysteresis effects in neuro-cognitive models in the future.